Mejne vrednosti ostankov zdravilnih učinkovin in pomožnih snovi po čiščenju v proizvodnih prostorih - Kragelj Lapanja, Nevenka (Farmacevtski vestnik, 2017)
When producing different medicinal products in shared facilities or equipment, the potential for cross-contamination is a concern. To prevent the effect of contaminants to the effectiveness and/or safety of medicines, the manufacturing equipment needs to be cleaned regularly and the carry-over limits for cleaning validation studies need to be adequately determined. In 2014, an EMA 'Guideline on setting health based exposure limits for use in risk identification in the manufacture of different medicinal products in shared facilities' (EMA/CHMP/ CVMP/ SWP/169430/2012) was published. The guideline describes an approach to review and evaluate pharmacological and toxicological data of individual active substances and thus enable determination of threshold levels. The derivation of such a threshold should be based on the use of PDE and ADE. However, other scientifically justified approaches can be used. One of them is the approach that is based on the use of occupational safety data. This article summarises the differences in setting the exposure limits between the two approaches, as well as between the PDE approach and approach used before EMA guideline. The approach in line with EMA guideline is considered more appropriate to establish appropriate exposure limits. In some cases, however, the old method is still suitable, or even more conservative than the new approach.
Keywords: drug; exposure limits of medicinal products residues; LOAEL; manufacturing facilities; mejne vrednosti ostankov zdravil; NOAEL; PDE; proizvodni prostori; Zdravila